IOT BASED WIFI DOOR LOCK USING ESP 32-CAM & FACE DETECTION SYSTEM - Ms. Konade S. B; Miss. Potdar M. D; Miss. Patil P. P; Miss. Swami V.S. (International Engineering Journal For Research & Development, 2021)
Door plays an important role in home security. To secure the house, the occupants of the house will always have the door locked. However, sometimes the house occupants forget to lock the door due to hurry when leaving the house, or they may doubt whether they have locked the door or not. We propose an application called Door Security System which is based on Android using Internet of Things (IoT) technology to monitor the status of the door, controlling the door and increasing security in a house. MQTT cloud is utilized as the communication protocol between smartphone and door lock system. PIR sensor is implemented in the door lock to detect the movement near the door, while touch sensor is installed on the door handle to recognize the human hand. Should the door is opened by force, the alarm will ring and send notification to alert the house occupant on the existence of intruder in the house. The evaluation results show that motion detection sensor can detect movement accurately up to 1,6 meters ahead, and messages published between smart phone and door lock are encrypted properly so messages are safely sent. The Project reported here in and titled as “Design & Implementation of an IoT Networked Contactless Doorway Security System for Remote Monitoring and Control using ESP32-CAM and a Cloud Server”. People want security in everyplace possible when they are into their homes or away from their homes. An anti-theft system is a device or method used to prevent or deter the unauthorized intrusion or trespassing activity in its coverage area. The implemented system was developed in combination of hardware and software. It's a unique security system made with low cost wireless camera and sensors which ensured remote monitoring and control of doorways. The system empowered the user to monitor the doorway by capturing images using a highperformance wireless camera i.e. ESP32-CAM connecting other devices and sensors in an IoT network. For other tasks like to control electronic door lock remotely, to click more pictures as well as to get notifications a cloud server application „Blynk‟ was used over the smart-phone. A major challenge was to develop this dynamic system with zero error, Real-time response and smooth performance, viable, smart and feasible..